Studying technology-based XXI Century Learning using MOOC in Education - Verawardina, Unung; Ramadhani, Dochi; Susanti, Wilda; Lubis, Arina Luthfini; Simeru, Arden; Ambiyar, (International Journal of Psychosocial Rehabilitation, 2020)
21st century learning is in line with technological developments. The various educational institutions have experienced digital transformation in a broad scope. At present, learning is no longer limited to one place, but can be broadly in various places between universities and countries. This article discusses about the technology-based 21st Century Learning using MOOC in Education. The results examined provide an insight to educational institutions in understanding and implementing technology-based XXI century learning through MOOC, containing MOOC learning technology, the advantages and the disadvantages, MOOC platforms and models, and course content.